AGAMA DAN SPIRIT EKONOMI: STUDI ETOS KERJA DALAM KOMPARASI PERBANDINGAN AGAMA - Wasisto Raharjo Jati (Al Qalam, 2018)
This study aimed to analyze relation among religion and economy in developing work ethic. the original thesis concerning relation of religion and work ethic initiated by Max Weber in his study entitled Protestant Ethic and Spirit Capitalism. In Weberian perspective, religion take important role that developing values of work ethics e.g. rationalism, asceticism, and "calling" are encouraging human to work hard in the world. This study aimed to elaborating Weber’s thesis within comparing work ethic in others religion. Library research used as research methodology in this research. The result showed, basically, work ethic invented in many religion; nevertheless, adapted to the context of socio-cultural in society. Keywords: Work Ethic, Calvinism, Max Weber's Thought, Economic Spirit.